CONFLICT RESOLUTION CONCEPT: IMPLEMENTATION OF CCA-FM MODEL IN MERANTI FOREST MANAGEMENT UNIT, SOUTH SUMATRA - Ja Posman Napitu; Aceng Hidayat; Sambas Basuni; Sofyan Sjaf (Indonesian Journal of Forestry Research, 2018)
Local communities have been using forest land area far before Industrial Forest Plantation (HTI) permit was granted. The overlapping land use among different users potentially leads to conflict. This paper studies conflict resolution creatively and collaboratively with forest management. Conflict resolution is based on the Creativity and Collaboration Action - Forest Management (CCA-FM) model on field exploration that created participation pattern of all parties in the vision of forestry science principles as the basis of policymaking. Convergent Parallel Mixed Method (CPMM) approaches with Rapid Land Tenure Assessment (RaTA) were used. Results show that claim of the community as the owner of the authority rights and dominance of the local elites, greatly affect the action situation. However, the policy options taken by the government towards policy outcomes do not tend to consider the field conditions. The CCA-FM model has been implemented in five villages. The community strongly supports the government to devolve the management rights to the community and to facilitate the transfer of knowledge, technology, market information, supporting all parties, and collaboration on business license management. Research results recommend the CCA-FM model could be a basis for building village self-reliance and improving the performance of the Forest Management Unit (FMU).